Redox cell biology and genetics / A Redox cell biology and genetics / edited by Chandan K. Sen, Lester Packer - Sen, Chandan K.; Packer, Lester (Redox cell biology and genetics, 2002)
The critically acclaimed laboratory standard for more than forty years, Methods in Enzymology is one of the most highly respected publications in the field of biochemistry. Since 1955, each volume has been eagerly awaited, frequently consulted, and praised by researchers and reviewers alike. Now with more than 300 volumes (all of them still in print), the series contains much material still relevant today?truly an essential publication for researchers in all fields of life sciences
Includes bibliographical references and indexes. - Print version record
Keywords: Electronic books